2020
DOI: 10.34172/aim.2020.03
|View full text |Cite
|
Sign up to set email alerts
|

The Exponentially Increasing Rate of Patients Infected with COVID-19 in Iran

Abstract: Background: Coronavirus, the cause of severe acute respiratory syndrome (COVID-19), is rapidly spreading around the world. Since the number of corona positive patients is increasing sharply in Iran, this study aimed to forecast the number of newly infected patients in the coming days in Iran. Methods: The data used in this study were obtained from daily reports of the Iranian Ministry of Health and the datasets provided by the Johns Hopkins University including the number of new infected cases from February 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 15 publications
(24 reference statements)
1
28
0
6
Order By: Relevance
“…General characteristics of reviewed studies: We found 13 articles and 10 reports and included eight published articles / preprint manuscripts [16][17][18][19][20][21][22][23] and three reports [13,24,25]. From the 13 found articles, three articles were kept for a next version of this review [8][9][10], one article was excluded because it was not an epidemic estimation study, and one article was excluded because of absent minimum necessary details on methods. From the 10 found reports, three were included, four were excluded because they were not an independent epidemic modeling study, three excluded because of absent minimum necessary details on methods, and one was excluded because it was not an epidemic estimation study.…”
Section: Resultsmentioning
confidence: 99%
“…General characteristics of reviewed studies: We found 13 articles and 10 reports and included eight published articles / preprint manuscripts [16][17][18][19][20][21][22][23] and three reports [13,24,25]. From the 13 found articles, three articles were kept for a next version of this review [8][9][10], one article was excluded because it was not an epidemic estimation study, and one article was excluded because of absent minimum necessary details on methods. From the 10 found reports, three were included, four were excluded because they were not an independent epidemic modeling study, three excluded because of absent minimum necessary details on methods, and one was excluded because it was not an epidemic estimation study.…”
Section: Resultsmentioning
confidence: 99%
“…There have been many articles using the ARIMA model to predict the trend of COVID-19 in different countries [9,16]. In Iran, Moftakhar et al [17] used the ARIMA model and artificial neural network to predict the daily new COVID-19 infections, which showed that the ARIMA model was more accurate. Ceylan [16] estimated the prevalence of COVID-19 in Italy, Spain, and France, with M A P E ( I t a l y ) = 4 .…”
Section: (4) Predictionmentioning
confidence: 99%
“…Most recently, a large number of models have been used to nowcast and forecast the epidemic patterns of COVID-19 pandemic around the world, such as ARIMA model, 3,[30][31][32] machine-learning model, 8 spatiotemporal approach, 5 Bats-Hosts-Reservoir-People transmission network model, 33 data mining approach based on a 3rd degree polynomial curve, 7 SEIR or SIR model, 18,34 internet search-interest based model, 9 ad hoc, 35 fixed-effects linear model, 36 adaptive neuro-fuzzy inference system (ANFIS) model, 37 etc. However, most of these models are focused on a shortterm estimation for the COVID-19 incidence, mortality, or prevalence, and they can only unearth the linear or nonlinear components in a given series.…”
Section: Introductionmentioning
confidence: 99%